SISTEM MONITORING DAN KONTROL TANAMAN DENGAN SENSOR KELEMBAPAN DAN SENSOR NPK BERBASIS IoT (INTERNET OF THINGS) - Aryo Setio, Rakhen; Saputra, Anja; Yudhi, Yudhi; Lesta, Lesta (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Modern agriculture demands efficiency and accuracy in resource management, particularly in monitoring soil moisture and the content of essential macronutrients such as nitrogen, phosphorus, and potassium. This study aims to design and implement a plant monitoring and control system based on the Internet of Things that integrates soil moisture and NPK sensors. The system is designed to collect real-time soil condition data and transmit it to an XAMPP server, allowing smartphone access via a web application. The research method includes hardware and software design, sensor testing, data analysis of the monitoring results and the automatic control of irrigation and fertilization. Data analysis is carried out by comparing sensor measurement results with the standard requirements of the plants. The test results show that the system can effectively monitor and control plant conditions, provide accurate information, and facilitate remote agricultural management. In conclusion, this system can improve the efficiency of water and fertilizer use and crop productivity, thus supporting precision and sustainable agriculture.